School Hours and Maternal Labor Supply. (18th January 2019) - Shure, Nikki
Summary: This paper examines the effect of extending the primary school day on maternal labor supply. I exploit the staggered nature of the recent German reform to extend school hours and assess whether or not gaining access to a full day school increases the likelihood that mothers enter into the labor market or extend their hours worked if already employed. I use the German Socio‐Economic Panel data set (GSOEP) and link it to a self‐collected school‐level data set with geographical information software (GIS). Using a flexible difference‐in‐difference approach in the estimation of linear probability and logit models, I find that the policy has a statistically significant effect of approximately five percentage points at the extensive margin, drawing more women into the labor market. I find no significant effect of the policy at the intensive margin; women who were already working do not extend their hours worked. This has implications for policies to extend the school day that do not correspond to the working day.